Glial Control of Synapse Number in Healthy and Diseased Brain - Lee, Eunbeol; Chung, Won-Suk (Frontiers in Cellular Neuroscience, 2019)
Glial cells are emerging as crucial players that mediate development and homeostasis of the central nervous system (CNS). In particular, glial cells are closely associated with synapses, and control synapse formation, function, plasticity, and elimination during the stages of development and adulthood. Importantly, it is now increasingly evident that abnormal glial function can be an active inducer of the initiation and progression of various neurodegenerative diseases. Here we discuss recent developments on the physiological roles of glial cells in brains, and propose that synapse loss, which is a common characteristic of several neurodegenerative diseases, can be initiated by mis-regulation of normal glial function.